Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1111/mec.15724
|View full text |Cite
|
Sign up to set email alerts
|

Leech blood‐meal invertebrate‐derived DNA reveals differences in Bornean mammal diversity across habitats

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 105 publications
0
41
0
Order By: Relevance
“…2015). The presence of all these species have been confirmed in the area using leech-based iDNA sampling (Drinkwater et al . 2020).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…2015). The presence of all these species have been confirmed in the area using leech-based iDNA sampling (Drinkwater et al . 2020).…”
Section: Discussionmentioning
confidence: 87%
“…Now the focus is moving towards the development of standardised invertebrate collection methods and biodiversity analyses (Abrams et al . 2019, Drinkwater et al . 2020) allowing for greater integration of the two techniques (Tilker et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, aquatic vertebrate or invertebrate communities can be detected with eDNA metabarcoding of water samples (Shaw et al, 2016;Stat et al, 2017;Valentini et al, 2016), animal diets can be detected from eDNA metabarcoding of feces (De Barba et al, 2014;Massey et al, in press;Roffler et al, 2021), and plants and fungi can be detected by eDNA metabarcoding of pollen or ice core samples (Bell et al, 2019;Kraaijeveld et al, 2015;Varotto et al, 2021). Similarly, an emerging technique to monitor the diversity of terrestrial vertebrates uses animalfeeding invertebrates (whether feeding upon blood, flesh, or scat) as direct sources of species' DNA and is called invertebrate-derived DNA (iDNA) (Batovska et al, 2018;Calvignac-Spencer et al, 2013;Drinkwater et al, 2019Drinkwater et al, , 2020Gogarten et al, 2020;Kocher et al, 2017; P. S. Lee et al, 2016;Schnell et al, 2012;van der Heyde et al, 2020;D. W. Yu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Leeches (Drinkwater et al, 2019;Schnell et al, 2012Schnell et al, , 2018Weiskopf et al, 2018) and carrion flies (Calvignac-Spencer et al, 2013; P. S. Lee et al, 2016;Lynggaard et al, 2019;Rodgers et al, 2017) have been the primary sources of validating iDNA metabarcoding for monitoring vertebrate biodiversity. The limited number of studies utilizing metabarcoding with leeches or carrion flies as iDNA samplers have shown that both taxa effectively profile biodiversity in remote or difficult to access environments such as tropical forests (Drinkwater et al, 2020;Gogarten et al, 2020; P. S. Lee et al, 2016;Weiskopf et al, 2018). There is a growing literature of comparing carrion flies as iDNA sources for metabarcoding to camera trapping (Gogarten et al, 2020; P. S. Lee et al, 2016;Rodgers et al, 2017) but even with their utility for profiling animal diversity, neither leeches nor carrions flies are widely collected for other research purposes.…”
Section: Introductionmentioning
confidence: 99%